Emulgel: A New Platform For Topical Drug Delivery - VIKAS SINGLA,; SEEMA SAINI,; BAIBHAV JOSHI,; A.C RANA, (International Journal of Pharma and Bio Sciences, 2012)
When gel and emulsion are used in combined form the dosage form are referred as emulgel. Emulgels have emerged as one of the most interesting topical delivery system as it has dual release control system i.e. gel and emulsion. The major objective behind this formulation is delivery of hydrophobic drugs to systemic circulation via skin. In fact presence of a gelling agent in water phase converts a classical emulsion in to emulgel. The emulgel for dermatological use has several favorable properties such as being thixotropic, greaseless, easily spreadable, easily removable, emollient, non-staining, water-soluble, longer shelf life, bio-friendly, transparent & pleasing appearance. Various penetration enhancers can potentiate the effect. So this can be used as better topical drug delivery systems over present conventional systems available in market.